Mediating museums : exhibiting material culture in Tunisia (1881-2016) - Rey, Virginie, 1978- (Studies in the History and Society of the Maghrib, 2019)
This book documents and interprets the trajectory of ethnographic museums in Tunisia from the colonial to the post-revolutionary period, demonstrating changes and continuities in role, setting and architecture across shifting ideological landscapes. The display of everyday culture in museums is generally looked down upon as being kitsch and old-fashioned. This research shows that, in Tunisia, ethnographic museums have been highly significant sites in the definition of social identities. They have worked as sites that diffuse social, economic and political tensions through a vast array of means, such as the exhibition itself, architecture, activities, tourism, and consumerism. The book excavates the evolution of paradigms in which Tunisian popular identity has been expressed through the ethnographic museum, from the modernist notion of 'indigenous authenticity' under colonial time, to efforts at developing a Tunisian ethnography after Independence, and more recent conceptions of cultural diversity since the revolution. Based on a combination of archival research in Tunisia and in France, participant observation and interviews with past and present protagonists in the Tunisian museum field, this research brings to light new material on an understudied area.